M19 Differences in patient and physician viewpoints of the management of idiopathic pulmonary fibrosis (ipf). (15th November 2017) - Maher, TM; Swigris, JJ; Kreuter, M; Wijsenbeek, M; Axmann, J; Ireland, L; Nathan, SD
Abstract : Introduction: A majority of patients with IPF do not receive antifibrotic therapy with pirfenidone or nintedanib. We investigated viewpoints about IPF care and treatment amongst patients, and amongst physicians with a 'watch and wait' approach (WWP) or a proactive approach (PP). Methods: Participants from Europe and Canada took part in an online survey. Responses were collected from patients with IPF, and from physicians responsible for initiation of IPF treatment who had consulted with ≥5 patients with IPF within 3 months. A mixture of WWP (monitor for ≥4 months post-diagnosis in ≥50% of patients before initiating antifibrotic) and PP (initiate antifibrotic <4 months post-diagnosis in majority of patients) were recruited. Results: 43 patients and 254 physicians were surveyed between September and October 2016. Only 56% of patients felt that they received enough information at diagnosis: 58% were advised that IPF is progressive; 44% discussed prognosis; and 49% were told about treatment options. Although the majority of patients (93%) preferred to receive information from their physician, most patients sought additional information about IPF (86%), treatment (81%), and/or prognosis (76%). Most patients (86%) felt that the ability of antifibrotic treatments to slow IPF progression was more important than side-effect profiles. Overall, 86% of patients who had received antifibrotic therapy felt confident in managing side effects. WWP were less likely to discuss IPF prognosis than PP, even when asked specifically by patients (Table). 62% and 38% of patients with 'mild' IPF were treated with an antifibrotic <4 months post-diagnosis by PP and WWP, respectively. WWP were more concerned about treatment side effects than PP (28% vs 17%, respectively); PP were more concerned about disease progression than WWP (83% vs 72%, respectively). Conclusions: We identified a disparity between the information patients want at diagnosis and the information they receive from physicians. Furthermore, Results suggest that PP may be more confident with the benefit-risk profile of antifibrotic treatment than WWP. A belief in effective treatment options may aid conversation with patients regarding their IPF diagnosis, thereby enabling patients to make informed treatment decisions.